Membrana de alumina anódica: comportamento da microestrutura e estudo das propriedades ópticas após tratamento térmico - Timoteo Júnior, José Flávio (2012)
Thin commercial aluminum electrolytic and passed through reactions was obtained with anodic alumina membranes nanopores. These materials have applications in areas recognized electronic, biomedical, chemical and biological weapons, especially in obtaining nanostructures using these membranes as a substrate or template for processing nanowires, nanodots and nanofibers for applications noble. Previous studies showed that the membranes that have undergone heat treatment temperature to 1300° C underwent changes in morphology, crystal structure and optical properties. This aim, this thesis, a study of the heat treatment of porous anodic alumina membranes, in order to obtain and to characterize the behavior changes structures during the crystallization process of the membranes, at temperatures ranging between 300 and 1700° C. It was therefore necessary to mount a system formed by a tubular furnace resistive alumina tube and controlled environment, applying flux with special blend of Ag-87% and 13% N2, in which argon had the role of carrying out the oxygen nitrogen system and induce the closing of the pores during the densification of the membrane. The duration of heat treatment ranged from 60 to 15 minutes, at temperatures from 300 to 1700° C respectively. With the heat treatment occurred: a drastic reduction of porosity, grain growth and increased translucency of the membrane. For the characterization of the membranes were analyzed properties: Physical - thermogravimetric, X-ray diffraction, BET surface area; morphological - SEM, EDS through compositional and, optical absorbance, and transmittance in the UV-VIS, and FTIR. The results using the SEM showed that crystallization has occurred, densification and significant changes in membrane structure, as well as obtaining microtube, the BET analysis showed a decrease in specific surface area of the membranes has to 44.381 m2.g-1 to less than 1.8 m2.g-1 and in the analysis of transmittance and absorbance was found a value of 16.5% in the range of 800 nm, characteristic of the near infrared and FTIR have confirmed the molecular groups of the material. Thus, one can say that the membranes were mixed characteristics and properties which qualify for use in gas filtration system, as well as applications in the range of optical wavelength of the infra-red, and as a substrate of nanomaterials. This requires the continuation and deepening of additional study